'P. Machuca - Ph.D. Code Repository' - Antonio Machuca Varela, Pablo (Cranfield University, 2021)
This reposity contains examples of simulations contained in P. Machuca's Ph.D. thesis (Cranfield University, 2020):"MISSION DESIGN AND AUTONOMOUS DEEP-SPACE OPERATIONS FOR THE LOW-COST EXPLORATION OF ASTEROIDS USING CUBESATS"
Keywords: Pablo'; 'Machuca'; 'Varela'; 'Ph.D.'; 'Code'; 'Repository'; 'Trajectory Design'; 'Autonomous Navigation'; 'Mission Design'; 'CubeSats'; 'Asteroid Exploration'; 'Deep Space'; 'Aerospace Engineering'